Analisis user experience terhadap OPAC Perpustakaan UIN Sunan Kalijaga Yogyakarta menggunakan teori Jacob Nielsen - Imroatun Shaleha; Sri Rohyanti Zulaikha; Adzkiyah Mubarokah (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
UIN Sunan Kalijaga Yogyakarta Library is a campus library that has been known by the public as a technology-based digital library because UIN Sunan Kalijaga Yogyakarta Library has used the Online Public Access Catalog (OPAC) system in providing information services to users. However, Sunan Kalijaga UIN Library Yogyakarta has never conducted an assessment and evaluation of the User Experience of its OPAC system. In fact, if this system is managed properly and gets a good User Experience, then the number of users will also increase and have an impact on the increasing number of visits and the efficiency of the services provided. The purpose of this study is to analyze the User Experience of the OPAC system of Sunan Kalijaga UIN Library Yogyakarta with Jacob Nielsen's theory which consists of five criteria, namely Learnability, efficiency, memorability, errors, and satisfaction. The method used is qualitative descriptive by racing on Jacob Nielsen's theory which has five basic principles in demonstrating ease in interface design using OPAC. The result of this study is that OPAC Library UIN Sunan Kalijaga Yogyakarta has four which are included in Jacobb Nielsen's theory, namely learnibility, efficiency, memorability, and errors. One of these criteria that is not included in Jacob Nielsen's theory is the point of satisfaction, this is because OPAC Library UIN Sunan Kalijaga Yogyakarta has difficulty in knowing the status of the collection to be searched, whether the collection is under loan from other students or not. Keywords: User Experience; OPAC; Jacob Nielsen; Digital Library.